2017
DOI: 10.1016/j.jaut.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Flexible peptide recognition by HLA-DR triggers specific autoimmune T-cell responses in autoimmune thyroiditis and diabetes

Abstract: Autoimmune polyglandular syndrome 3 variant (APS3v) refers to the co-occurrence of autoimmune thyroiditis (AITD) and type 1 diabetes (T1D) within the same individual. HLA class II confers the strongest susceptibility to APS3v. We previously identified a unique amino acid signature of the HLA-DR pocket (designated APS3v HLA-DR pocket) that predisposes to APS3v. We hypothesized that both thyroid and islet peptides can be presented by the unique APS3v HLA-DR pocket, triggering AITD+T1D together. To test this hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…Human leukocyte antigen (HLA) class II genes and their alleles are considered as the pivotal factors of HT. HLA and its alleles may confer the strongest susceptibility to autoimmune poly-glandular syndrome 3 variant (APS3v), which is associated with the occurrence of HT [24,25]. In the present study, we identified not only classic HT susceptibility genes, but also several novel unreported gene markers, thereby supporting the credibility of our bioinformatics analysis.…”
Section: Discussionsupporting
confidence: 73%
“…Human leukocyte antigen (HLA) class II genes and their alleles are considered as the pivotal factors of HT. HLA and its alleles may confer the strongest susceptibility to autoimmune poly-glandular syndrome 3 variant (APS3v), which is associated with the occurrence of HT [24,25]. In the present study, we identified not only classic HT susceptibility genes, but also several novel unreported gene markers, thereby supporting the credibility of our bioinformatics analysis.…”
Section: Discussionsupporting
confidence: 73%
“…Four islet and thyroid peptides (Tg.1571, GAD.492, TPO.758, and TPO.338) were identified with the ability to bind to the HLA-DR binding pocket, being presented by antigen-presenting cells and elicited a T cell response. Both thyroid and islet peptides can bind to this flexible binding pocket and induce thyroid and islet specific T cell responses, thus triggering T1D and AITD in the same individual ( 78 ). Potential mechanisms how HLA genes activate endocrine autoimmunity and predispose to both T1D and AITD, even if the autoantigenic peptides are distinct, are shown in Figure 2 .…”
Section: The Genetic Linkmentioning
confidence: 99%
“… 37 , 38 HLA genes are strongly linked with thyroid autoimmunity in patients with T1DM, demonstrating that some genetic determinants within the HLA region are involved in both T1DM and AITD. 35 , 36 , 39 , 40 The HLA DRB1*0405/DQA1*0301/DQB1*0401 haplotype confers susceptibility in patients with T1DM and GADAb-positive AITD, whereas individuals with the HLA DRB1*0803/DQB1*0601 haplotype are more susceptible to AITD but not to anti-islet autoimmunity. 5 , 41 In addition to high-risk HLA DR-DQ haplotypes, HLA class I A and C alleles also appear to be associated with T1DM in Filipino patients.…”
Section: Genetics and Autoimmunitymentioning
confidence: 99%